2‐Tridecanone impacts surface‐associated bacterial behaviours and hinders plant–bacteria interactions. (30th March 2018) - López‐Lara, Isabel M.; Nogales, Joaquina; Pech‐Canul, Ángel; Calatrava‐Morales, Nieves; Bernabéu‐Roda, Lydia M.; Durán, Paloma; Cuéllar, Virginia; Olivares, José; Alvarez, Laura; Palenzuela‐Bretones, Diana; Romero, Manuel; Heeb, Stephan; et al.
Summary: Surface motility and biofilm formation are behaviours which enable bacteria to infect their hosts and are controlled by different chemical signals. In the plant symbiotic alpha‐proteobacterium Sinorhizobium meliloti, the lack of long‐chain fatty acyl‐coenzyme A synthetase activity (FadD) leads to increased surface motility, defects in biofilm development and impaired root colonization. In this study, analyses of lipid extracts and volatiles revealed that a fadD mutant accumulates 2‐tridecanone (2‐TDC), a methylketone (MK) known as a natural insecticide. Application of pure 2‐TDC to the wild‐type strain phenocopies the free‐living and symbiotic behaviours of the fadD mutant. Structural features of the MK determine its ability to promote S. meliloti surface translocation, which is mainly mediated by a flagella‐independent motility. Transcriptomic analyses showed that 2‐TDC induces differential expression of iron uptake, redox and stress‐related genes. Interestingly, this MK also influences surface motility and impairs biofilm formation in plant and animal pathogenic bacteria. Moreover, 2‐TDC not only hampers alfalfa nodulation but also the development of tomato bacterial speck disease. This work assigns a new role to 2‐TDC as an infochemical that affects important bacterial traits and hampers plant–bacteria interactions by interfering with microbial colonization of plant tissues.